Synthesis, In Vitro, In Vivo and In Silico Antidiabetic Bioassays of 4-Nitro(thio)phenoxyisobutyric Acids Acting as Unexpected PPARγ Modulators: An In Combo Study - Blanca Colin-Lozano; Héctor Torres-Gomez; Sergio Hidalgo-Figueroa; Fabiola Chávez-Silva; Samuel Estrada-Soto; Julio Cesar Almanza-Pérez; Gabriel Navarrete-Vazquez (MDPI AG, 2022)
Four isobutyric acids (two nitro and two acetamido derivatives) were prepared in two steps and characterized using spectral analysis. The mRNA concentrations of PPARγ and GLUT-4 (two proteins documented as key diabetes targets) were increased by 3T3-L1 adipocytes treated with compounds 1-4, but an absence of in vitro expression of PPARα was observed. Docking and molecular dynamics studies revealed the plausible interaction between the synthesized compounds and PPARγ. In vivo studies established that compounds 1-4 have antihyperglycemic modes of action associated with insulin sensitization. Nitrocompound 2 was the most promising of the series, being orally active, and one of multiple modes of action could be selective PPARγ modulation due to its extra anchoring with Gln-286. In conclusion, we demonstrated that nitrocompound 2 showed strong in vitro and in vivo effects and can be considered as an experimental antidiabetic candidate.